Pedro Antonio de Alarcón, El Niño de la Bola. Ed. de Ignacio Javier López. Catédra, Madrid, 2014; 380 pp. (Letras Hispánicas, 735). - Canals Piñas, Jordi (El Colegio de México, 2014)
Reseña del libroEl Niño de la Bola.